MECHANISMS OF IMMUNE DISBALANCE FORMING IN PATIENTS WITH VIRAL INFECTIONS OF RESPIRATORY TRACT, AND NEW OPPORTUNITIES OF IMMUNOTHERAPY - N.V. Khoroshilova ("Paediatrician" Publishers LLC, 2009)
Viruses are the leading etiological factor of recurrent infections of respiratory tract. Experimental trials showed that influenza, respiratory syncytial and rhinovirus render toxic action on the elements of inborn and acquired immunity, resulting in hyperproduction of pro-inflammatory cytokines with damaging effect on tissues and organs. According to this fact application of immunomodulator treatment seems to be quite actually. At the present times, there's only one immunomodulator, recommended by WHO for the treatment of patients with recurrent respiratory infections. It is pidotimod (Imunorix). The article presents data from experimental clinical trials, studying influence of pidotimod on parameters of inborn and acquired immunity and, accordingly, on the clinical course of respiratory infections in children's and adults. Different double-blinded placebo-controlled studies showed that pidotimod decreases a severity and duration of respiratory infections, improves functional state of respiratory epithelium. Thus, pidotimod is perspective immunomodulator for the prophylaxis and treatment of respiratory tract. Key words: children, pidotimod, viral infections, prophylaxis, treatment. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(5):56-61)